Importance of organizational culture: a model for increased engagement - Sayma M; Treharne TL; Williams HR (Journal of Multidisciplinary Healthcare, 2016)
Meelad Sayma, Tomos Luke Treharne, Hywel Rhys WilliamsPeninsula College of Medicine and Dentistry, Plymouth, UKWe read with great interest the article by Nilsen et al,1 discussing how nursing leaders perceive their interactions and support levels from both peers and those in more senior leadership positions – in this case the municipal health director. Of particular interest was the conclusion of the paper, calling for greater coherence between different levels of leadership in the Norwegian health care setting. View original paper by Nilsen et al